The Efficiency of Sputum Cell Counts in Cystic Fibrosis - Lata Jayaram; N Renee Labiris; Ann Efthimiadis; Helen Vlachos-Mayer; Frederick E Hargreave; Andreas P Freitag (Canadian Respiratory Journal)
BACKGROUND: Technical factors relating to processing viscid sputum in cystic fibrosis (CF) and their influence on the reproducibility and validity of cell counts need to be evaluated. In addition, the methods need to be standardized so that they can be applied clinically and in research.